Turks' prejudice against Kurds and Syrians :|the role of contact, identification, and threat - Fırat, Mustafa. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study examined the effect of imagined contact on Turks’ prejudice against Kurds and Syrians, with a focus on the moderating role of in-group identification and the mediating role of intergroup threat in the imagined contact-prejudice relationship. An experiment was conducted among 335 Turkish undergraduate students (154 males, 180 females; Mage = 20.30, SD = 1.38). Participants were presented with measures assessing their ethnic and national identification, realistic and symbolic threat, and explicit and implicit prejudice after the imagined contact manipulation. The results showed that imagined contact did not have a prejudice-reducing effect. Accordingly, there was neither a moderating role of in-group identification nor a mediating role of intergroup threat. However, identification and threat significantly predicted prejudice. Ethnic identification was positively related to prejudice against Kurds and Syrians, while national identification was negatively related to prejudice against only Kurds. Realistic and symbolic threat were positively associated with prejudice against both groups. The results were discussed in relation to social identity theory, common in-group identity model, and intergroup threat theory. Theoretical refinement to the imagined contact hypothesis was also discussed.|Keywords : Social contact, social identity, intergroup threat, prejudice
Keywords: Refugees, Syrian -- Turkey.; Kurds -- Turkey.; Prejudices -- Turkey.; Threat (Psychology) -- Syrian.; Group identity.; Social conflict.